Scale and growth analysis of Sea trout (Salmo trutta L.) using object j caught in Etneelva in 2019 - Bhattarai, Sangita (University of South-Eastern Norway, 2020)
There is a decline in sea trout (Salmo trutta L.) population in central Norway since 1970s. While the reason behind this reduction until now unknown but marine mortality can be one of the reasons. Sea trout, known as anadromous brown trout, shares its life both in fresh water and sea water and shows a complex life history. Young sea trout migrates to sea and undergo smoltification commonly at age two, where they attain proper growth and return to freshwater during winter or late autumn for spawning or over-wintering. Sea trout, unlike Atlantic salmon is less studied and is very little is known. In this study, age and growth of sea trout caught in Etneelva in 2019 is estimated by reading scales. Use of scales to estimate age and growth patterns has been very popular since 1980’s as they are less expensive, non-lethal and less-time consuming as compared toother calcified structures. 1236 sampled sea trout scale images were collected from Etne lab and analysed using a free image processing software called image j and its macro objectj.4 out of 1232 were excluded from sample due to insufficient information and other 237 scale were replacement scales they were not used in back calculation as it underestimates the age estimation. Annuli in scales of sea trout are used to determine age and reconstruct growth histories. Back- calculation based on the assumption that fish length/growth is proportional to otolith or scale length is done. In salmonids, linear relationship is assumed between scale and body. Results showed that sea trout caught in etneelva was of age 1-15years. Majority of the young parr smolted at age three and four and a most at age two which was a common age for smolts. Rapid variations in smolt growth rate was noticed for the first 3 years in sea after smoltification. This may be due to change in water temperature and food availability. Back-calculated first winter length for most sea trout was between 40-60 mm, but some were very high for first year length. Back- calculated winter length for sea trout ...